Kriteria Kesahihan Hadis Menurut Nashiruddin Albani dan Ahmad Al-Ghumari - Hanifa, Mia Syahrina; Masrur, Ali; Khaeruman, Badri (Jurnal Riset Agama, 2022)
The purpose of this study is to find out the criteria for the validity of hadith according to Nashiruddin Albani and Al-Ghumari and to find out the differences and similarities of the criteria for the validity of hadith according to Nashruddin Albani and Al-Ghumari. The research Â Â method used is comparative study. The results of this study showed that technically, the two hadith scholars have their own characteristics in researching the validity of a hadith. The criteria of shahih hadith according to the two hadith scholars do have similarities and differences with some other hadith scholars so as to cause some controversy.